Helping the Rich get Richer: A Re-assessment of the Income Distributional Trend in Hong Kong. - Wong, Mathew Y. H. (Asian Studies Review, 2017)
Although many are under the impression that income inequality in Hong Kong has been continually on the rise, the picture presented by official statistics is mixed. This article suggests that official statistics, due to limitations in their design, have underestimated the impact of the top earners. Utilising taxation data, a continuous and strong growth in inequality can be identified when the distribution among taxpayers is considered, providing an alternative picture of inequality in Hong Kong. It is argued that the surge in income inequality is driven in part by the rich earning more rather than by more people becoming rich. The Hong Kong government, instead of adopting redistributive measures to alleviate the situation, has exacerbated inequality through policy choices that strongly favour the richest group. Although these actions might be explained in relation to the political influence wielded by the business sector and the upper class, the social implications of inequality cannot be neglected. Apart from a stronger demand for democracy, perceptions of income inequality and the pro-rich bias in the political system significantly affect people’s political views, as seen in the support for the recent Occupy Movement.